Restorative justice: a substantive, intergenerational and ecological approach in the Amazon Region of Brazil - Salm, Joao (Contemporary justice review, 2021)
From the report of a case in which restorative justice references were used to address a conflict involving chestnuts gathers and family farmers in the Brazilian Amazon, the article reflects on the conditions of applying restorative justice concepts and procedures to treat socio-environmental conflicts. Restorative philosophy adopts a substantive vision concerned with an intergenerational and ecological ethic that can contribute to the realization of justice and the sustainability of peace in Amazonian scenarios. In order to face an alienating vision that disregarding human multidimensionality, the authors suggest a holistic understanding of reality that understands nature as part of what we are, that we inhabit, with which we are ineluctably interconnected and that is impacted by human actions, especially those of apolitical character and economical. This comprehending leads them to an ecological and intergenerational perspective of restorative justice that transcends the de-identification of humanity with nature. Understood in this way, restorative justice implies responsibility towards human beings and nature. This means looking for solutions that meet not only the needs of the actors directly and indirectly affected by a particular offense; in addition to intersubjective issues, it concerns the satisfaction of demands for social justice and environmental conservation, inviting humanity to render intergenerational accounts. The article concludes that an ecological and intergenerational view of restorative justice requires exercises of imagination and effective practice capable of facing the tangles of the humanity-nature relationship within extended perspectives that account for considering the multidimensionality of the human experience.